Chronic pain and depression. Correlation and treatment - A review of current literature - Wołoszyn, Barbara; Rzeźnik, Patrycja; Sobczyk, Maciej; Stachera, Weronika; Guzowska, Julia; Chajnowska, Aleksandra; Borowy, Aleksandra; Suchcicka, Wiktoria; Zach, Małgorzata; Stępień, Julia (Quality in Sport, 2025)
Introduction and purpose The comorbidity of chronic pain and depression is a prevalent medical challenge faced by both patients and healthcare providers. The purpose of this review is to examine the correlation between these conditions and to analyze current treatment methods. State of knowledge The relationship between chronic pain and depression is undoubtedly complex. Over a quarter of individuals with persistent pain experience depressive symptoms, and more than half of psychiatric patients also suffer from chronic pain. This comorbidity affects all age groups- adolescents, adults, and older adults. Research indicates that pain involving multiple body regions is associated with a higher risk of depression. Currently, no single treatment effectively addresses both conditions simultaneously. The most commonly used approach involves pharmacological interventions, particularly antidepressants such as tricyclic antidepressants (TCAs) and serotonin-noradrenaline reuptake inhibitors(SNRIs). However, various non-pharmacological methods-especially when combined with medication -can also be beneficial. Material and methods This review was compiled through an extensive analysis of the PubMed, Cochrane, and Google Scholar databases. We primarily focused on articles published between 2020 and 2025 that included keywords such as: “depression,” “chronic pain,” “major depressive disorder,” “antidepressants,” and “nociplastic pain.” Conclusion The co-occurrence of chronic pain and depression is extremely common. Antidepressants remain a standard treatment option for managing both conditions. However, non-pharmacological methods can complement traditional approaches. Despite the range of available treatment strategies, there is no universally effective or standardized therapy for managing depression comorbid with chronic pain. The absence of clear protocols for managing these issues highlights the necessity for future research.